2018
DOI: 10.18009/jcer.330925
|View full text |Cite
|
Sign up to set email alerts
|

Internet Usage Habits and Internet Usage in Educational Studies of Vocational School Students

Abstract: Internet is the easiest way to access information. It provides positive contributions to individual and surroundings, in learning and information era. At this point the answers of the questions: ‘How do young people use internet and how much do they use internet for their education?’ come into prominence. In order to find the answers; a questionnaire prepared by resarchers and Young Internet Addiction Test- Short Form (YIAT-SF) was used on ‘Health Services Vocational High School’ students, in this study. 3.4 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this study, the participants' internet addiction scores were 28.64 ± 7.51 on average, and 53% of them were moderate, 1.5% were at are very high‐risk for internet addiction (Table 2). Yakıncı et al (2018) reported students' average internet addiction score was 27.64 ± 8.65 (for female students), and 28.60 ± 9.65 (for male students), and 3.4% of them were high‐risk for addictions. In other recent studies, adolescents' internet addiction score were found to be 30.90 ± 8.29 (Savcı & Aysan, 2017); and among university students on average 23.7 ± 7.9% and 5.1% severe addicttion risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the participants' internet addiction scores were 28.64 ± 7.51 on average, and 53% of them were moderate, 1.5% were at are very high‐risk for internet addiction (Table 2). Yakıncı et al (2018) reported students' average internet addiction score was 27.64 ± 8.65 (for female students), and 28.60 ± 9.65 (for male students), and 3.4% of them were high‐risk for addictions. In other recent studies, adolescents' internet addiction score were found to be 30.90 ± 8.29 (Savcı & Aysan, 2017); and among university students on average 23.7 ± 7.9% and 5.1% severe addicttion risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out with 'Health Services Vocational High School' students, revealed that, the average internet usage was found to be 5 hours daily among students. When students were asked to enumerate the internet sites they use, the result was: social media, news sites, movie and series sites, educational and informational content sites, play sites, e-mail, shopping sites, and sexual content sites in order of usage preference (Yakıncı et al, 2018)  Game arcades that have turned into an important socialization area for children in Turkey, can affect children in many ways and children prefer digital games because they find it amusing, fun, enjoyable and exciting (Aslan et al, 2019). Thus, spending reasonable time on their phones.…”
mentioning
confidence: 99%